Diseño arquitectónico de un centro deportivo de alto rendimiento utilizando criterios de arquitectura bioclimática - Chávez Vallejo, Romina Milena (2024)
The project of the high performance sports center in Santa Cruz, Galapagos, focuses on the creation of spaces that help meet the needs of high performance athletes, due to the deficiency in the implementation of sports facilities, which allow their preparation in sports at national and international level, being of impediment to the physical preparation of athletes. The design integrates criteria of bioclimatic architecture, which seeks to optimize the performance of athletes, through considerations such as environmental factors, and designs that favor efficient training.....